(untitled) (Intent Research Scientific Journal, 2023)
In world beekeeping, no bee breed has been artificially created so far, each region has its own bee breeds and populations adapted to its geographical location and climatic conditions. Such bee breeds differ sharply from bees acclimatized in other areas by their morphological characteristics and beneficial economic properties.